Frequency-selective hybrid beamforming for mmWave full-duplex - Andrea Guamo-Morocho; R. López-Valcarce (IEEE Int. Conf. Acoustics, Speech and Signal Processing (ICASSP), 2023)
We study beamforming cancellation for a full-duplex (FD) wideband millimeter wave (mmWave) point-to-point bidirectional link in which both multicarrier-based nodes transmit and receive simultaneously and on the same frequency. The focus is on hybrid architectures in which the analog subblock of the beamformer, common to all subcarriers, is fully-connected and based on phase shifters with finite resolution, to avoid frontend saturation by mitigating FD-induced self-interference in the analog domain.
Keywords: full-duplex; mmWave; rodin